Global perspectives on teacher learning: improving policy and practice - Schwille, John; Dembélé, Martial (UNESCO: International Institute for Educational Planning, 2007)
Keywords: C:International; ___working_potential_duplicate

Global perspectives on teacher learning: improving policy and practice - Schwille, Jack; Dembelé, Martial (UNESCO-IIEP, 2007)
This booklet looks at all forms of teacher learning, formal and informal, from teachers. own early schooling, through their... | Find, read and cite all the research you need on ResearchGate
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Global perspectives on teacher learning: improving policy and practice - Schwille, Jack; Dembelé, Martial (UNESCO-IIEP, 2007)
This booklet looks at all forms of teacher learning, formal and informal, from teachers. own early schooling, through their... | Find, read and cite all the research you need on ResearchGate
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Global Perspectives on Teacher Learning: improving policy and practice | Request PDF - Schwille, Jack; Dembelé, Martial (UNESCO-IIEP, 2007)
Request PDF | Global Perspectives on Teacher Learning: improving policy and practice | Incl. bibl. This booklet looks at all forms of teacher learning, formal and informal, from teachers. own early schooling, through their... | Find, read and cite all the research you need on ResearchGate
Keywords: ⛔ No DOI found